Effect of Charge Bump Position Shifting on Negative Resistance and Noise Performance of Lo–Hi–Lo IMPATT. Issue 4 (4th July 2022) - Banerjee, J.; Mitra, M.
ABSTRACT: In this paper, the effect of position shifting of charge bump on different microwave parameters, such as the negative resistance, noise measure, quality factor, and series resistance of one-dimensional different compound semiconductor-based DDR IMPATT structures, has been studied using the advanced computer iterative method. A comparison of a crucial parameter, negative resistance, of these devices is obtained for different charge bump positions at different frequencies of a Ka band. The noise measure has been carried out also varying with these different charge bump positions at the depletion layer as noise measure strongly depends on the negative resistance value. Quality factor also varies for these changes of the charge bump position. The noise measurement plays an important role in the choice of structures and operating frequency of the IMPATT device. So, throughout the Ka band, the parameters of these different compound semiconductor-based IMPATT diodes for different charge bump positions are measured and compared and will be well suited for the optimum design in the Ka band.